2007
DOI: 10.1016/j.ijsolstr.2006.07.017
|View full text |Cite
|
Sign up to set email alerts
|

An analysis of dislocation nucleation near a free surface

Abstract: Molecular dynamics analyses of defect-free aluminum single crystals subject to bending are carried out to investigate dislocation nucleation from free surfaces. A principal aim of the analyses is to provide background for the development of dislocation nucleation criteria for use in discrete dislocation plasticity calculations. The molecular dynamics simulations use an embedded atom potential for aluminum. Bending is imposed on a strip by specifying a linear variation of displacement rate on opposite edges. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
12
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(13 citation statements)
references
References 29 publications
1
12
0
Order By: Relevance
“…The resolved shear stress of ͑111͓͒121͔ slip system reaches consequently a maximum stress of 1.7 GPa for 0 = −7.8% in the compression areas. This result is in good agreement with the work of Liu et al, 16 which shows that for a cell of a single bent Al crystal defined with the following axes ͑O x ͒ = ͓111͔, ͑O y ͒ = ͓101͔, and ͑O z ͒ = ͓121͔, dislocations can be also nucleated from the free surfaces of the crystal. With such an orientation, the observed partial dislocations nucleated in ͕111͖ slip planes rapidly self-annihilate, with a slip distance of 1.39 nm.…”
Section: ͑4͒supporting
confidence: 92%
See 1 more Smart Citation
“…The resolved shear stress of ͑111͓͒121͔ slip system reaches consequently a maximum stress of 1.7 GPa for 0 = −7.8% in the compression areas. This result is in good agreement with the work of Liu et al, 16 which shows that for a cell of a single bent Al crystal defined with the following axes ͑O x ͒ = ͓111͔, ͑O y ͒ = ͓101͔, and ͑O z ͒ = ͓121͔, dislocations can be also nucleated from the free surfaces of the crystal. With such an orientation, the observed partial dislocations nucleated in ͕111͖ slip planes rapidly self-annihilate, with a slip distance of 1.39 nm.…”
Section: ͑4͒supporting
confidence: 92%
“…14 It was recently demonstrated that the presence of tilt boundaries results in the formation of buckling blisters with lower energy than the classical elastic ones. 15 Finally, Liu et al 16 studied by molecular dynamics the behavior of bent Al single crystals, which is quite similar to the mechanical solicitations of a buckled structure. They demonstrated that partial dislocations are nucleated in compressive areas near the free surfaces at a resolved shear stress of 1.78 GPa.…”
mentioning
confidence: 95%
“…However, the Schmidt factor for the most favorable slip system in the [1,1,1] nanowire is larger in tension than that in compression but the residual compressive stresses counteract this effect producing an equal value of the yield stress in tension and compression. Even though Diao et al [2] found that the critical resolved shear stress does not change appreciably with the cross-sectional area of the nanowire and that it can be used as a criterion for the nucleation of defects, Liu et al [5] and Miller and Rodney [6] have stated that the slip system with the highest resolved shear stress is not always activated at the yield point.…”
Section: Introductionmentioning
confidence: 99%
“…At present no surface nucleation criterion for use in a discrete dislocation plasticity analysis has been developed. In fact, there is no basis for presuming that a critical Peach-Koehler force is an appropriate criterion for dislocation nucleation at a surface (see Liu et al, 2007). In the absence of a more appropriate surface nucleation criterion, we use a similar criterion as for bulk sources but with possibly different source strengths t n surf .…”
Section: Constitutive Relations For Dislocation Plasticitymentioning
confidence: 99%